Bamako Transit - Lixon, Céline (France, 2011)
To be an "adventurer" in Africa means to leave your homeland behind in search of a new life. Thousands of hopefuls from surrounding countries flock to Algeria with the intention of later migrating to Europe. Legislation prohibits this, however, and states that these people must be expelled from Algeria - many are sent to the neighboring country of Mali, where they must remain without legal status.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films